2012 IEEE International Conference on Mechatronics and Automation 2012
DOI: 10.1109/icma.2012.6283171
|View full text |Cite
|
Sign up to set email alerts
|

A rotary magnetorheological fluid damper for pathological tremor suppression

Abstract: -This study explores the development of a new configuration of rotary magnetorheological fluid damper (MR damper) for pathological tremor suppression. In order to be attached to portable rehabilitation robot developed for practical application in robot assisted therapy, the proposed MR damper aims for design of compact size, light weight and enough output torque (about 4.5 Nm). An approach to form serpentine magnetic path by employing an offset electromagnetic coil and an asymmetric rotor is utilized to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The dynamic behaviour of the designed system was improved by using various control methods. Yang et al (Yang et al, 2012) used a compact and light weight rotary MR damper in pathological tremor suppression.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic behaviour of the designed system was improved by using various control methods. Yang et al (Yang et al, 2012) used a compact and light weight rotary MR damper in pathological tremor suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the robot grip can be safely manoeuvred into its target position using just one direct current (DC) motor. Yang et al (2012) showed that providing MR dampers in manipulator joints led to reduction of the jitters effect during the positioning of the robot arm.…”
Section: Introductionmentioning
confidence: 99%